Implementasi Kebijakan Sistem Zonasi dalam Proses Penerimaan Peserta Didik Baru (Studi Pada Kantor Dinas Pendidikan dan kebudayaan Kabupaten Aceh Utara) - Fauzan Fauzan; Irwan Doni; Rudi Kurniawan; Muryali Muryali (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The aim of the state is to educate the nation's life and for that every Indonesian citizen has the right to obtain quality education according to his interests and talents regardless of social status, race, ethnicity, religion and gender. The National Education System must be able to ensure equal distribution of educational opportunities, improve quality as well as the relevance and efficiency of education management to face challenges in accordance with the demands of changes in local, national, and global life so that education reforms are planned, directed, and sustainable. This study aims to analyze the implementation of the zoning system policy in the process of accepting new students at State Elementary School 3 Lhoksukon, North Aceh Regency. The type of research is qualitative research with data analysis used is data reduction, data presentation, and drawing conclusions or verification and in this study the informants were determined purposively. The results of the study indicate that this rule works well, because the requirements that must be met by prospective students are quite strict and are implemented by the State Elementary School 3 Lhoksukon, North Aceh Regency, although there are several separate problems due to the public's lack of understanding of this regulation.